The relationships between the structural video game characteristics, video game engagement and happiness among individuals who play video games. (December 2016) - Laffan, Derek A.; Greaney, John; Barton, Hannah; Kaye, Linda K.
Abstract: The present study investigated the relationships between the structural video game characteristics (e.g. social, presentation and punishment features), video game engagement components (e.g. flow, immersion and psychological absorption) and general happiness among an international sample of individuals who play video games. Online questionnaires were completed by 207 participants who simultaneously had their favourite or most played video game in mind while completing the questionnaires. The results indicated that flow was significantly predicted when individuals rated punishment (e.g. lose a life, restart a level) and presentation (e.g. audio and graphics) characteristics as present and important. A negative and weak relationship was found between general happiness and flow. It was concluded that the punishment and presentation features aid in the facilitation of a flow experience, as the punishment gaming aspects may contribute to the task difficulty and degree of effort required to achieve a flow state, when playing video games. Highlights: Engaging video games research is evaluated in relation to theory and applications. A study is conducted using online questionnaires and correlational data analysis. Implications of results are provided for researchers and video game developers.